Hidradenitis suppurativa: chronology of the onset of the disease symptoms and their gender differences: a singlecenter case series of 100 patients - Kifayet Mammadlı; Aslı Bilgiç; Erkan Alpsoy (Galenos Publishing House, 2023)
Background and Design: The onset chronology of disease symptoms in patients with hidradenitis suppurativa (HS) and their gender differences have not yet been fully elucidated. We aimed to define the onset chronology of the disease symptoms and the socio-demographic and clinical characteristics. Materials and Methods: This single-center case series study included 100 consecutive patients. The disease symptoms for each patient were recorded in the time order of manifestations. Results: HS was more common in males (72%); 70% of the patients were overweight or obese. Smoking and alcohol consumption was significantly higher in males. The axilla was the most common onset area, followed by the inguinal and gluteal regions. The incidence of disease onset in the axilla in male and disease onset in the gluteus in female patients was significantly higher. Also, involvement of the pubis, perianal region, neck, back, and behind the ear was more common in males. The disease followed a more severe course in patients with the involvement of axilla, perianal, and inframammary areas (p<0.05). Conclusion: Besides being the most commonly involved site, axilla was the most common disease onset area in both genders; however, the incidence of disease onset in the gluteus is higher in females and the axilla in males. The male dominance observed in our cohort followed previous results reported from Türkiye, although differing from other countries. This suggests each society's unique genetic and environmental characteristics may influence the course and evolution of the disease.